2017
DOI: 10.1002/ps.4715
|View full text |Cite
|
Sign up to set email alerts
|

The impact of restrictions on neonicotinoid and fipronil insecticides on pest management in maize, oilseed rape and sunflower in eight European Union regions

Abstract: BACKGROUNDIn 2013, the European Commission restricted the use of three neonicotinoids (clothianidin, imidacloprid and thiamethoxam) and the pyrazole fipronil, which are widely used to control early‐season pests. Here, we used original farm survey data to examine the impact of the restrictions on pest management practices in eight regional case studies including maize, oilseed rape and sunflower in seven European Union (EU) countries.RESULTSIn four case studies, farmers switched to using untreated seeds as no a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 35 publications
2
42
1
4
Order By: Relevance
“…However, the toxicity of fluralaner to honeybees needs to be considered before it can be registered as an insecticide for agricultural production. In 2014, the binding profile of radioligand [H] fluralaner to honeybee head was reported . However, the activities of fluralaner to honeybee in vivo and on its molecular target remain to be determined.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, the toxicity of fluralaner to honeybees needs to be considered before it can be registered as an insecticide for agricultural production. In 2014, the binding profile of radioligand [H] fluralaner to honeybee head was reported . However, the activities of fluralaner to honeybee in vivo and on its molecular target remain to be determined.…”
Section: Discussionsupporting
confidence: 89%
“…Insecticides, which target the γ‐aminobutyric amino acid (GABA) receptor (GABAR), including dieldrin, endosulfan, fipronil, ethiprole, etc ., play very important roles in the control of agricultural insect pests. However, similar to neonicotinoid insecticides, fipronil has been restricted for use in recent years due to its possible negative effect on the bee population …”
Section: Introductionmentioning
confidence: 99%
“…An increase in area treated to compensate for the seed dressing ban was also identified in an evaluation of its impact on pest management in oilseed rape across Europe. 37 From this current study, 1.14 and 0.77 million ha of WOSR were treated to combat the threat of CSFB in autumn 2014/15 and autumn 2015/16, respectively. The clear difference between the two seasons can be partly explained by: the reduction in area of WOSR grown between the two seasons, the presence of a DA in 2015/16 with clear differences for farms using treated vs non-neonicotinoid treated seed, and awareness of increasing resistance of CSFB to pyrethroids.…”
Section: Insecticide Use To Combat Csfbmentioning
confidence: 96%
“…With the exception of the limited case-study-based findings following the EU neonicotinoid ban (Kathage et al 2018;Scott and Bilsborrow 2019;Dewar 2017), there are no large scale empirical studies that document and estimate the impacts of widespread neonicotinoid use. In addition, there is no existing work that uses farm-level data to estimate and disentangle the impacts of both NeoST and GE trait adoption on the likelihood of using specific insecticide groups, nor do any previous studies estimate their impacts on toxicity risk for different species.…”
Section: These Insecticide Regression Models Are Informative About Thmentioning
confidence: 99%
“…Organophosphates are widely considered more dangerous for applicators and mammals than neonicotinoids (Hurley and Mitchell 2017), and pyrethroids are highly toxic to aquatic life and often as toxic to non-target insects (Douglas and Tooker 2016). Empirical evidence of substitution into these insecticides has recently been documented in the EU, where it has been found that the EU neonicotinoid ban has led to increases in the use of alternative soil and foliar applied insecticides in 3 both maize (Kathage et al 2018) and oilseed rape production (Kathage et al 2018;Scott and Bilsborrow 2019;Dewar 2017).…”
Section: Introductionmentioning
confidence: 99%